Effects of quality grade, aging period, blade tenderization, and degree of doneness on tenderness of strip loin - C.D. George-Evins; John A. Unruh; James L. Marsden; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2000)
We used 162 strip loins to determine the influence of different quality grades, aging periods, blade tenderization passes, and degree of doneness on thawing and cooking loss and Warner-Bratzler shear force (WBS, tenderness). Select (SEL), Choice (CHO), and Certified Angus Beef™ (CAB) strip loins were aged for 7, 14, or 21 days and not tenderized (0X) or blade tenderized one (1X) or two (2X) times. Steaks from each strip loin were assigned randomly to final endpoint cooking temperatures of 150, 160, and 170°F. For steaks aged 7 days, all quality grade and blade tenderization treatments had similar (P>.05) WBS. For steaks aged 14 days, CHO steaks had lower (P<.05) WBS than SEL steaks, CAB tended (P=.07) to have lower WBS than SEL, 2X steaks had lower (P<.05) WBS than 1X steaks, and 1X steaks had lower (P<.05) WBS than 0X steaks. For steaks aged 21 days, CAB steaks had lower (P<.05) WBS than CHO steaks, CHO steaks had lower (P<.05) WBS than SEL steaks, and 2X steaks had lower (P<.05) WBS than 1X steaks. Among the 0X and 2X groups, CAB and CHO steaks had lower (P<.05) WBS than SEL steaks. For the 1X group, only CAB steaks had lower (P<.05) WBS than SEL steaks. Blade tenderization improved tenderness of strip steaks but should be combined with high quality grades, increased aging, and lower endpoint cooking temperatures to achieve maximum tenderness.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Tenderness; Blade tenderization; Aging; Quality grade